Story in the Qur'an and Its Relevance in Early Childhood Education - Ali Imran Sinaga; Afrahul Fadhilah Daulay; Rosmawati Lubis (Britain International for Academic Research (BIAR) Publisher, 2020)
The purpose of this study is to find out: the disclosure of stories in the Qur'an, and the relevance of the stories in the Qur'an to early childhood education. The research method used is qualitative. Data collection techniques carried out by documentation and interviews. Data collection procedures are carried out with the stages of data collection, data reduction, data presentation, and drawing conclusions. Checking the validity of the data is carried out with four criteria, namely credibility, transferability, dependability, and confirmability. Research findings show the story in the Qur'an means the stories or news of the Qur'an about events or events that befell the people or previous people, both involving human nations and the nations of the jinn and angels, even nations of the animal group who acts like a human. The story in the Qur'an is the best story, it is a true story and contains a lot of